Behavioural Determinants of Functionality of Farmer Producer Organisations in Punjab - Singh, Manjinder; Tiwari, Devinder; Monga, Sarang; Rana, Rajesh K. (Indian Journal of Extension Education, 2021)
Small and marginal farming communities of Indian agriculture account for more than 85%of the total farming households. They face the challenges of land fragmentation, high cost of inputs and inability to market their produce efficiently. To tackle these challenges, policy makers came up with the model of farmers’ mutual cooperation through Farmer Producer Organisations (FPOs). This study conducted in Punjab analyses the behavioural factors responsible for functionality of FPOs. A random selection of 150 members from 5 functional and 5 non-functional FPOs (i.e., 15 respondents from each selected FPO) was made and the respondents were interviewed personally. The findings revealed that the members (including management) of the functional FPOs had higher risk bearing capacity, greater economic motivation and more innovativeness as compared to the respondents from non-functional FPOs. Similarly, respondents from functional FPOs were socially, economically and managerially more empowered than the non-functional FPOs. Business skills of the members, including the managerial members, of functional FPOs were also better as compared to those from the non-functional FPOs. Regression estimates revealed that the functionality, better academic qualification, bigger land holding and joint family system were responsible for the higher net annual income of the respondents.
Keywords: Business skills; Entrepreneurial characteristics; Farmer producer companies; Non-functional FPOs; Socio-economic empowerment; Sustainability